2020
DOI: 10.3390/genes11101119
|View full text |Cite
|
Sign up to set email alerts
|

Heterochiasmy and Sexual Dimorphism: The Case of the Barn Swallow (Hirundo rustica, Hirundinidae, Aves)

Abstract: Heterochiasmy, a sex-based difference in recombination rate, has been detected in many species of animals and plants. Several hypotheses about evolutionary causes of heterochiasmy were proposed. However, there is a shortage of empirical data. In this paper, we compared recombination related traits in females and males of the barn swallow Hirundo rustica (Linnaeus, 1758), the species under strong sexual selection, with those in the pale martin Riparia diluta (Sharpe and Wyatt, 1893), a related and ecologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 50 publications
(37 reference statements)
4
16
0
Order By: Relevance
“…The chromosome reconstruction (2n = 80) matches our cytogenetic analysis (Fig. 1a; Additional file 1: Supplementary Note), and is in line with the current literature on pachytene karyotypes of the barn swallow (41). Based on the original chicken chromosome classification (42) and our chromosome sizes (Additional file 1: Table S3, Supplementary Note), we define chromosomes 1-6 and Z as macrochromosomes, 7-13 and W as intermediate-size chromosomes, and 14-39 as microchromosomes.…”
Section: Resultssupporting
confidence: 88%
“…The chromosome reconstruction (2n = 80) matches our cytogenetic analysis (Fig. 1a; Additional file 1: Supplementary Note), and is in line with the current literature on pachytene karyotypes of the barn swallow (41). Based on the original chicken chromosome classification (42) and our chromosome sizes (Additional file 1: Table S3, Supplementary Note), we define chromosomes 1-6 and Z as macrochromosomes, 7-13 and W as intermediate-size chromosomes, and 14-39 as microchromosomes.…”
Section: Resultssupporting
confidence: 88%
“…Phylogeny of birds where within sex recombination rates have been estimated using linkage mapping, or cytogenetic analysis of chiasma counts using MLH1 foci or recombination nodules (indicated by *). The underlying data is provided in Table S5 using data compiled in (Malinovskaya et al . 2020b) and other sources.…”
Section: Resultsmentioning
confidence: 99%
“…Related to this point, Z‐linked regions recombine only in males, requiring a potentially extreme male recombination bias for the effective recombination rate of the Z to match that of autosomes. However, a recent study found intriguing evidence for female‐biased recombination rates in barn swallows (Malinovskaya et al, 2020). While we did not estimate recombination rates here, these factors together argue that low rates of recombination on the Z chromosome contribute to low genetic diversity through linked selection.…”
Section: Discussionmentioning
confidence: 99%